Growth factor and hypoxia-inducible factor alpha content in the retina of male Wistar rats in experimental diabetic retinopathy and the effect of cellular protein kinase blockade - Usenko, K. O.; Strubchevska, Olena; Rykov, S. O.; Babenko, M. S.; Strubchevska, Kateryna; Kozyk, Oleksandra; Ziablitsev, S. V.; Kozyk, Marko (Frontiers in Endocrinology, 2025)
BackgroundDiabetic retinopathy (DR) is a leading cause of vision loss in patients with diabetes mellitus (DM). Hypoxia-driven overexpression of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-1α (HIF-1α) is central to diabetic retinopathy (DR) pathogenesis. The use of cellular protein kinase inhibitors is a promising approach for correcting pathological changes in DR.ObjectiveTo determine the effect of pharmacological blockade of cellular protein kinases with sorafenib on the expression of VEGF and HIF-1α in the retina in experimental diabetic retinopathy.Material and methodsDiabetes mellitus (DM) was induced in male rats by administration of streptozotocin (50 mg/kg). Animals were divided into three groups: in group 1 (n=15) rapid-acting insulin at a dose of 30 U was injected intraperitoneally, in group 2 (n=15) insulin was combined with sorafenib (per os 200 mg), and in the control group (n=15) no treatment of hyperglycemia was performed. 5 animals were used to obtain baseline data (intact). The drugs were administered every other day, starting from day 7 after streptozotocin injection, for 3 months. Immunohistochemical studies were performed using monoclonal mouse antibodies against VEGF. Sections were additionally stained with hematoxylin. The content of VEGF and HIF-1α in retinal tissue lysates was determined by Western blotting. Membranes with proteins were incubated with monoclonal antibodies against VEGF and HIF-1α. After the initial incubation, the membranes were washed and treated with anti-species secondary antibodies conjugated to horseradish peroxidase. Statistica 10 software was used for statistical analysis. Descriptive statistics were calculated, including means and their standard errors. Sample averages were compared using analysis of variance (ANOVA), with p-values less than 0.05 considered statistically significant.ResultsUnder the conditions of experimental DR, the content of VEGF in retinal tissues increased significantly and after 3 months of observation increased 6,8-fold for the dimeric form and 27.1-fold for the monomeric form (p<0,05) compared to intact animals. Under the same conditions, the level of HIF-1α was also significantly increased (39.6-fold; p<0.05). When insulin was administered, the content of VEGF fractions in the retina decreased by an average of 1,4-1,5 times (p<0,05), and the heterogeneity of the response to its administration was observed. The use of sorafenib with insulin in all cases blocked the increase in VEGF content caused by DR. Insulin administration reduced HIF-1α levels by 1,4-fold (p<0,05) compared to the control, whereas combined sorafenib and insulin treatment reduced HIF-1α expression to undetectable levels. Immunohistochemical examination revealed a progressive increase in the intensity of VEGF-positive staining in the retina during experimental DR, as well as the development of its degenerative changes - edema, ischemia, pathological angiogenesis, neurodegeneration, and disruption of retinal layer organization. The use of insulin did not cause changes in the retinal pattern, whereas the combined use of sorafenib and insulin prevented the development of both morphological signs of DR and an increase in the intensity of VEGF-positive staining.ConclusionThe significance of VEGF and HIF-1α upregulation in the pathogenesis of DR and the effectiveness of their correction by pharmacological blockade of cellular protein kinases with sorafenib have been established.